2016
DOI: 10.1002/advs.201600108
|View full text |Cite
|
Sign up to set email alerts
|

Local Structural Distortion Induced Uniaxial Negative Thermal Expansion in Nanosized Semimetal Bismuth

Abstract: The corrugated layer structure bismuth has been successfully tailored into negative thermal expansion along c axis by size effect. Pair distribution function and extended X‐ray absorption fine structure are combined to reveal the local structural distortion for nanosized bismuth. The comprehensive method to identify the local structure of nanomaterials can benefit the regulating and controlling of thermal expansion in nanodivices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 42 publications
1
32
0
Order By: Relevance
“…Fort he pure MoS 2 or MoSe 2 monolayers,t he coordination numbers of Mo-S or Mo-Se reduced slightly, while their disorder degrees increased remarkably compared with bulk counterparts,w hich implied the presence of an oticeable structure distortion that in turn helped to their structural stability. [14] More importantly,T able 1also revealed that the coordination numbers of Mo-S and Mo-Se in the MoSeS alloy monolayers were 2.4 and 2.6, which indicated that the ratio of Sa nd Se was roughly 1:1, fairly consisting with the corresponding ICP,X RF and EDX analysis in Figure S6-7 and Table S1. Furthermore,t he MoSeS alloy monolayers exhibited shortened Mo À Sb ond length and lengthened Mo-Se bond length relative to the MoS 2 and MoSe 2 monolayers,w hich indicated af urther distorted structure,fairly agreeing with the optimized crystal structure by DFT calculations.…”
Section: Angewandte Chemiementioning
confidence: 69%
“…Fort he pure MoS 2 or MoSe 2 monolayers,t he coordination numbers of Mo-S or Mo-Se reduced slightly, while their disorder degrees increased remarkably compared with bulk counterparts,w hich implied the presence of an oticeable structure distortion that in turn helped to their structural stability. [14] More importantly,T able 1also revealed that the coordination numbers of Mo-S and Mo-Se in the MoSeS alloy monolayers were 2.4 and 2.6, which indicated that the ratio of Sa nd Se was roughly 1:1, fairly consisting with the corresponding ICP,X RF and EDX analysis in Figure S6-7 and Table S1. Furthermore,t he MoSeS alloy monolayers exhibited shortened Mo À Sb ond length and lengthened Mo-Se bond length relative to the MoS 2 and MoSe 2 monolayers,w hich indicated af urther distorted structure,fairly agreeing with the optimized crystal structure by DFT calculations.…”
Section: Angewandte Chemiementioning
confidence: 69%
“…Moreover, In 2020, Yu et al [29] reported that PEGylated Bi nanoparticles loaded with the model drug DOX, forming DOX@Bi-PEG nanoparticles, exhibit high photothermal conversion efficiency, strong NIR absorption, high DOX-loading efficiency as well as low cytotoxicity, having potential in chemo-photothermal therapy of cancer cells. Bi nanoparticles with an average diameter of 40 nm synthesized by chemical reduction method [300,301] were mixed with the amphiphilic PEGylated phospholipid (DSPE-PEG) in chloroform under continuous stirring overnight for the complete evaporation of chloroform solvent. The as-prepared Bi-PEG nanoparticles can be well dispersed in deionized water and can remain black, and Bi core is surrounded by a DSPE-PEG layer with the thickness of ≈8 nm.…”
Section: (26 Of 34)mentioning
confidence: 99%
“…For O3‐type oxides, the introduction of Li + is thought to be favorable for enhancing the electrochemical performance as Li + ions assist in the formation of an O3 phase, which eases the O3–P3 phase transformations . For instance, Na[Li 0.05 (Ni 0.25 Fe 0.25 Mn 0.5 ) 0.95 ]O 2 layered cathode materials demonstrated a very high capacity of 180.1 mA h g −1 at a 0.1C rate and excellent capacity retentions (0.5C rate: 92.1%) and good rate capabilities at various C‐rates, which are much higher than those of the lithium‐free cathode .…”
Section: Monoanion Compoundsmentioning
confidence: 99%
“…[90] For O3-type oxides, the introduction of Li + is thought to be favorable for enhancing the electrochemical performance as Li + ions assist in the formation of an O3 phase, which eases the O3-P3 phase transformations. [91] For instance, Na [Li 0.05 ) and good rate capabilities at various C-rates, which are much higher than those of the lithium-free cathode. [92] In addition to the above elemental strategies, nanoscale interface engineering is an effective tool to enhance the cathode performance.…”
Section: Mixed-cation Oxidesmentioning
confidence: 99%